Eros and the Christ: longing and envy in Paul's Christology - Fredrickson, David E. (Augsburg Fortress Publishers, 2013)
Intro -- Eros and the Christ -- Contents -- Abbreviations -- Translations from the Loeb Classical Library -- Introduction -- Notes -- Troubling Presence -- Notes -- Apostolic Sweetness -- Notes -- Kenōsis, or As the Snow Melts -- Notes -- Abduction Disregarded -- Notes -- Not Eaters of the People -- Notes -- The Politics of a Manbride -- Notes -- Conclusion -- Bibliography -- Index -- Biblical Index.